Occurrence–regression–recurrence of hepatocellular carcinoma without any intervention: A case report - Li, Weinan; Xiong, Yongfu; Shu, Xia; Li, Jingdong (Frontiers in Surgery, 2022)
Background Spontaneous regression of primary liver cancer is a rare event, and currently the exact pathogenesis of spontaneous tumor regression remains unclear. Case description Clinical information was collected from a patient with spontaneous regression of liver cancer at our center. The patient was a 41-year-old male. He was admitted to the hospital on 3 May 2019, due to aversion to fatty or greasy food, anorexia, loss of appetite, and abdominal distension. Laboratory examination results included hepatitis B surface antigen positivity, hepatitis B e antigen positivity, and hepatitis B core antibody positivity and tumor marker levels of alpha-fetoprotein 142,938.20 µg/L, abnormal prothrombin 4,599.91 mAU/ml, and carbohydrate antigen 19–9 82.05 U/ml. Upper abdominal enhanced computed tomography indicated right hepatocellular carcinoma with portal vein tumor thrombus formation. The patient declined any treatment. The tumor in the right lobe of the liver completely regressed after 1 year, and the patient is still undergoing follow-up. Conclusions We encountered a hepatocellular carcinoma patient who underwent spontaneous regression, but the exact pathogenesis remains unknown. Understanding the pathogenesis of spontaneous regression of hepatocellular carcinoma has the potential to contribute to the development of an effective treatment for hepatocellular carcinoma.